Isolation and characterization of actinomycetes against fungi causing anthracnose and leaf spot on rose plants - Dang, Thi Thanh Tam; Phung, Thi Thuy Tien; Nguyen, Duc Quan; Nguyen, Thanh Huyen (Vietnam Journal of Biotechnology, 2025)
Roses (Rosa spp., family Rosaceae) are one of the most iconic and beloved flowering plants worldwide. They serve not only as ornamental plants but also possess high economic value. However, rose production is currently threatened by various fungal diseases, including anthracnose, leaf spot, downy mildew, and powdery mildew, which reduce both productivity and quality. Therefore, the identification of actinomycete strains for the development of biological control agents is urgently needed. In this study, 17 strains of actinomycetes were isolated by using the gradient dilution and confrontation methods. Among them, the DT5 strain was selected for its strong antifungal activity, showing inhibition rates of 58.33% against anthracnose (R2 strain) and 52.17% against leaf spot (R3 strain) in roses. Colonies of the DT5 strain displayed a dry surface with concentric rings, initially white but gradually turning whitish-gray. Microscopic observation revealed elongated, branched hyphae and short, hook-shaped spore chains. Based on these morphological features, the DT5 strain was preliminarily classified as belonging to the genus Streptomyces. The DT5 strain was able to synthesize cellulase and effectively assimilate various carbon sources (such as glucose and sucrose) as well as nitrogen sources (including NaNO3, beef extract, and peptone). Additionally, the DT5 strain grew well at temperatures ranging from 30-37°C and at pH 5.0-7.0. Under optimal conditions, after 5 days of culture at pH 6.0, the DT5 strain significantly enhanced its antifungal activity against both the R2 and R3 strains with inhibition zones of approximately 15 mm and 20 mm, respectively. Our results suggest that the DT5 strain has good potential as a biological control agent against fungal diseases. However, future in vivo experiments under greenhouse and field conditions are required to validate its antifungal efficacy. These efforts will guide the development of effective and sustainable biocontrol products not only for managing fungal diseases in roses but also for potential application in protecting other economically important crops.